Breeding Centers, Private Ranches, and Genomics for Creating Sustainable Wildlife Populations. (9th October 2019) - Wildt, David; Miller, Philip; Koepfli, Klaus-Peter; Pukazhenthi, Budhan; Palfrey, Katy; Livingston, Gavin; Beetem, Dan; Shurter, Stephen; Gregory, Jimmy; Takács, Michael; Snodgrass, Kelley
Abstract: Human-induced changes to environments are causing species declines. Beyond preserving habitat (in situ), insurance (ex situ) populations are essential to prevent species extinctions. The Conservation Centers for Species Survival (C2S2) is leveraging space of breeding centers and private ranches to produce "source populations"—genetically diverse reservoirs that also support research and reintroductions. The initial focus is on four African antelopes. C2S2 has developed a program, the Source Population Alliance, that emphasizes animals living in spacious, naturalistic conditions in greater numbers than can be accommodated by urban zoos. Simulation modeling demonstrates how herds can rapidly increase population abundance and retain genetic diversity. Advances in genomics and resulting DNA data allow monitoring of genetic diversity and parentage as well as refined decision-making. This approach, neither pure in situ nor ex situ, but rather "sorta situ", is an innovative way of linking public and private sector resources to ensure that endangered species survive.